Risks and farmers’ investment in productive assets in Nigeria - Takeshima, Hiroyuki; Yamauchi, Futoshi (Wiley, 2012)
The majority of farmers in sub‐Saharan Africa (SSA) lack the means to mitigate the impact of risks associated with rainfall and commodity prices due to capital constraints and the imperfect insurance market in these countries. Because most SSA farmers are risk averse, they may be willing to invest in productive assets that can mitigate the impacts of such risks if their capital constraints are relaxed through external financial assistance. We test this hypothesis by using panel data on investment behavior of Nigerian farmers who received financial assistance on productive assets. The empirical results show that farmers facing higher rainfall risks are more likely to invest in irrigation pumps that can mitigate the impact of rainfall risks, while those facing higher risks of white gari price are more likely to invest in milling machines that enable them to process cassava into flour instead of gari, which supports our hypothesis.